Perioperative Outcomes of Using Different Temperature Management Strategies on Pediatric Patients Undergoing Aortic Arch Surgery: A Single-Center, 8-Year Study - Tong, Yuanyuan; Liu, Jinping; Zou, Lihua; Feng, Zhengyi; Zhou, Chun; Lv, Ruoning; Jin, Yu (Frontiers in Pediatrics, 2018)
Background: With the widespread application of regional low-flow perfusion (RLFP), development of surgical techniques, and shortened circulatory arrest time, deep hypothermia is indispensable for organ protection. Clinicians have begun to increase the temperature to reduce hypothermia-related adverse outcomes. The aim of this study was to evaluate the safety and efficacy of elevated temperatures during aortic arch surgery with lower body circulatory arrest (LBCA) combined with RLFP. Methods: We retrospectively analyzed data from 207 consecutive pediatric patients who underwent aortic arch repair with LBCA & RLFP between January 2010 and July 2017 and evaluated different hypothermia management strategies. The overall cohort was divided into three groups: deep hypothermia (DH, 20.0-25.0℃), moderate hypothermia (MoH, 25.1-30.0℃) and mild hypothermia (MH, 30.1-34.0℃). Results: The percentage of AKI-1 occurrences was significantly increased in the MH group (51.52%) compared to those in the DH (25.40%) and MoH (37.84%) groups (P=0.036); prolonged hospital stay occurrences were decreased with elevated temperature (DH 47.62%, MoH 28.83%, MH 18.18%, P=0.006). Neurological complications, peritoneal dialysis, hepatic dysfunction, 30-day hospital mortality, delay extubation occurrences were no significant among the groups. Logistic analysis showed that the MH group was negatively associated with post-op AKI-1 compared with the DH group [OR=0.329(0.137-0.788), P=0.013], no differences were found between the MoH and the MH group. Compared to other groups, the intubation time (P=0.006) and postoperative hospital stay (P=0.009) were significantly decreased in the MH group. Multivariate logistic analysis showed hypothermia levels were not significant with prolonged hospital stay. Conclusions: This retrospective analysis demonstrated that for pediatric patients undergoing surgeries with RLFP & LBCA, three different gradient temperature management strategies are available: deep, moderate, and mild hypothermia. Utilizing mild or moderate hypothermia is safe and feasible. Although the number of AKI-1 occurrences in the MH group was significantly increased compared to those in the other groups, further analysis showed no significance in the MoH and MH group, mild hypothermia management is as safe as others when used appropriately.